Avaliação das alterações craniofaciais associadas com a microtia - Peixoto, Cléuber Roberto (2021)
The craniofacial complex is composed of several structures that frequently undergo changes in their development, thus causing congenital alterations in growth, skeletal and dental development. Among developmental changes, Microtias stand out. The aim of this study was to evaluate the craniofacial changes associated with Microtia in non-syndromic patients. For this purpose, sixteen (n = 16) patients with Microtia treated at the Center for Integral Care of the Cleft Lip and Palate (CAIF), in the city of Curitiba, PR, Brazil, were evaluated and compared to a control group (n = 48). Sixty-four individuals participated in this study, 16 women (25%) and 48 men (75%), aged between 07-35 years. Retrospective analysis was performed, through the evaluation of the data present in the patients' medical records and imaging exams (teleradiography). To determine the skeletal changes, tracings and cephalometric analysis were performed in the case group and in the control group. The results were submitted to descriptive and inferential analyzes, using the Statistical for Social Science program, with a 95% confidence interval. It was observed that the cephalometric measurements were higher in the case group for ANB ( p = 0.044), FMA ( p <0.001), SN.GoGn ( p = 0.003), Y-axis ( p = 0.024), AFAI ( p <0.001) and 1-NB ( p = 0.014). The measurements 1.NA ( p = 0.018) and IMPA ( p = 0.029) were lower in the case group compared to the control group. It was concluded that in the case group the development of a Class II skeletal and dolichocephalic pattern prevailed, predisposition to verticalization of the upper incisors and the protrusion of the lower incisors. It was also possible to observe that in individuals with Microtia there is a tendency for the lower midline to be deviated to the affected side.